IMPLIKASI GERAKAN PEMBAHARUAN K.H. MAS ABDURAHMAN (1875-1943) DI BANTEN - Agus Kusman (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
AbstractThe beginning of the 20th century is the starting point of Islamic transformation in Indonesia. Various changes and renewal of social, economic, cultural, political to religious that appear massively like mushrooms in the rainy season. This is what is often called the culmination of modernization of Islam. In a vibrant atmosphere that is K.H. Mas Abdurrahman was present on the Indonesian history stage by contributing his energy, thought and spirit. K.H. Mas Abdurahman is a famous scholar in Banten. He initiated the establishment of the Mathla'ul Anwar madrasah, which then made the educational institution grow rapidly.Keywords: K.H. Mas Abdurahman, renewal, Banten